2019
DOI: 10.12912/23920629/113635
|View full text |Cite
|
Sign up to set email alerts
|

The role of soil fauna in the diversity of vegetation on the Carboniferous waste dump

Abstract: W pracy przedstawiono relacje między ilością fauny glebowej w zróżnicowaniu roślinności na zwałach pogórniczych. Dotychczas, badacze wiele uwagi poświęcali rozwojowi i zróżnicowaniu zespołów roślinnych na terenach poprzemysłowych uwzględniając m.in. hałdy skały płonnej. Znacznie słabiej poznano ilościowy i jakościowy udział wybranych grup mezo-fauny (nicienie i wazonkowce), w podłożu glebowym terenów poeksploatacyjnych. Poznanie tych zależności może mieć duże znaczenie praktyczne w planowaniu i realizowaniu pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…1). Other authors have also observed an increase in surface temperature of mining heaps with increasing height (Zając, Zarzycki, 2013;Surovka et al, 2017;Radosz et al, 2019). Due to high temperatures, no material was collected for testing.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…1). Other authors have also observed an increase in surface temperature of mining heaps with increasing height (Zając, Zarzycki, 2013;Surovka et al, 2017;Radosz et al, 2019). Due to high temperatures, no material was collected for testing.…”
Section: Resultsmentioning
confidence: 98%
“…The lowest average pH value was recorded at the top of the heap and the highest 1km from the top of the heap. Development of soil on mining waste heaps is a long-term process with significant contribution of biotic elements such as plants, microorganisms as well as soil fauna (Madej, 2002;Manu et al, 2017;Radosz et al, 2019). However, analyzes of the processes taking place on mining heaps mainly concern plant formations, while few studies are conducted on soil organisms inhabiting even the most degraded biotopes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The heaps are sites with habitat conditions different from those known from natural or semi-natural ones. The new man-created landscape forms are unique sites because they provide oligotrophic conditions (very poor in nutrients, such as phosphorus, nitrogen, sulfur, and carbon) mineral substrates; after many years of study, it has been shown that plants and animals have colonized them despite unfavorable conditions (Woźniak, 2010;Radosz et al, 2019). During the field research, the object was analyzed: "Makoszowy" (Zabrze, Sosnica; 50°16′22″ N, 18°44′43″ E); "Kostuchna" in Katowice (50°11′04″ N, 19°00′33″ E); "Murcki Boże Dary" in Murcki (50°11′21″ N, 19°02′07″ E); and "Wesoła" in Mysłowice (50°10′28′′ N, 19°5′44″ E).…”
Section: Site Descriptionmentioning
confidence: 99%